Kva styrer og kva styrker samspelet mellom barnehagepersonalet og foreldra? Ein studie om kommunikasjon mellom personale i barnehagen og fleirkulturelle foreldre med migrasjonsbakgrunn - Bergset, Gunnhild (Nordic Journal of Comparative and International Education (NJCIE), 2019)
The purpose of this article is to present and discuss some of the challenges in communication and interaction between a kindergarten staff and a parent group of migrant background. Based on an interview study conducted in a kindergarten, the article works to provides insight into and understanding of the kindergarten staff’s experiences and reflections from their efforts to improve communication and interaction practices in daily contact with parents of migrant background. The staff completed a kindergarten-based project of the initiative of the principal, in which all employees implemented specific communication and interaction measures. Then, in-depth interviews were conducted with all staff, as well as two focus group interviews with the same group of informants. The study is based on a dynamic concept of culture and highlights the challenges of asymmetric communication and the possibilities of communicating and interacting based on a resource perspective. The findings show that a movement has taken place towards dialogue-based reciprocity in the staff`s attitudes towards communication and interaction with these parents. The article argues that connection between a trying-out of concrete, professionally grounded practice and pedagogical reflection constitutes the necessary basis for a shift from a problem orientation to a resource orientation in communication and interaction. One outcome of this resource perspective was that the kindergarten staff recognized the parent`s experiences and perceptions as valuable for achieving the parental involvement required by kindergarten`s social mandate.